Human dignity. Concept acknowledgement and operationalization - Pyrrho, Monique; Cornelli, Gabriele; Garrafa, Volnei (Acta Bioethica, 2009)
Human dignity, present in the Declaration of Human Rights and also in recent international declarations on bioethics, has currently received harsh criticism as a bioethical term. The imprecise use of the term "dignity", without a clear definition, attributed to the individual as innate value and disconnected from its cultural references, culminates in its substitution for a clearer and operational concept: that of "autonomy". This work confronts the conceptual question of human dignity as a relational construction that is obtained through the acknowledgement of the other. In this manner this term, more ample and mobile historically than the principal concept of autonomy, incorporates in its definition and operationalization individual, social and cultural diversity.